Tumor necrosis factor alpha (TNF-alpha) and TNF-beta and their receptors in experimental cutaneous leishmaniasis. - de Kossodo, S (1994)
Experimental infection of BALB/c mice with Leishmania major leads to lesions which progress without healing and visceralization, reproducing the most severe forms of human leishmaniasis, while resistant mice like CBA spontaneously resolve lesions and develop protective immunity. Given the conflicting data pertaining to the role of tumor necrosis factor alpha (TNF) in Leishmania infection, we analyzed the expression of TNF, tumor necrosis factor beta (lymphotoxin), and TNF receptor type I (TNF-RI) and type II (TNF-RII) genes in vivo and correlated TNF gene expression in vivo with the production of biologically active TNF by lymphoid cells in vitro. No significant difference in the expression of TNF mRNA was found between susceptible and resistant strains of mice during the course of infection. The depletion of CD4+ T cells in vitro did not change the level of TNF mRNA in BALB/c lymph node cells but led to the total disappearance of TNF mRNA in CBA mice. Unprimed spleen cells did not produce detectable amounts of TNF, whereas 1 week after infection, TNF bioactivity was detected and increased in both strains of mice until 5 weeks of infection. While neutralization of TNF activity in vivo did not alter the course of infection in BALB/c mice, in CBA mice it led to an increase in lesion size and a delay in the healing process but did not interfere significantly with the outcome of infection. Finally, no significant difference in the levels of lymphotoxin, TNF-RI, or TNF RII mRNA expression was found between both strains. The information resulting from these investigations supports the notion that, in vivo, TNF is not the decisive factor responsible for the resistant versus susceptible phenotype in leishmania infection.